Contribution to the interpretation of the role of geoenvironment in extreme discharges of the Rosomačk River - Visok kraj - Nikić Zoran; Ristić Ratko; Marić Nenad; Milčanović Vukašin (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2018)
Annex to the interpretation of the role of geoenvironment in the formation of extreme discharges of the Rosomačka River provides exact and empirical evidence of the significance and the need for its knowledge. For hydrologically unstudied watercourses, especially for those which do not have continuity of discharges, the knowledge of the role of geoenvironment in the emergence of their extreme discharges contributes to a more realistic response to practical water management issues, protection against adverse effects of waters, defining the ecological aspect of watercourses under the influence of various changes in the near future (climatic, anthropogenic, hydrological), preserving the quality of river water, meeting the requirements of the EU Water Framework Directive 2000. The aim of the paper is to understand better the river systems and their runoffs in the form of high and low waters or complete drying up of hydrologically unstudied but also of hydrologically studied watercourses, and through the representation of the role of geoenvironment. On the concrete example of the Rosomačka River, a hydrologically unstudied watercourse, the significance of geoenvironment in the interpretation of its extreme discharges was emphasized. The contribution of the following elements of geoenvironment of the basin area was analyzed: lithological, neotectonic, hydrogeological and morphological. The research method is based on field research, quantitative geomorphological analysis, systematization and synthesis of the obtained results, as well as the analysis of published papers. Additionally, the contribution is reflected in emphasizing the need for communication between experts of various specialties dealing with hydrographic systems. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 37008]